THE INFLUENCE OF EMOTIONAL QUOTIENT TOWARD STUDENTS INDEPENDENCE LEARNING AND COMPREHENION OF MATHEMATICS CONCEPT - Tri Khoirul Jannah Khoirul Jannah; Dwi Avita Nurhidayah (EDUPEDIA, 2018)
The purpose of the research to: (1) describe the influence of emotional quotient toward students independence learning, (2) describe the influence of emotional quotient toward students comprehension of mathematics concept of Grade VII students in MTs. Ma'arif Darul Fattah Terpatih Galak Slahung Ponorogo. This research is quantitative researh was using survey method with population is all of student Grade VII in MTs. Ma'arif Darul Fattah with total of all student is 48 students. Then, students were choosed randomly for the sample with total 24 students. The data collection technique in this research are questionnaire and test, whereas the research instrument were using questionnaire of emotional quotient and independence learning also question test about comprehension of mathematics concept. The data analysis technique were using descriptive statistics and inferential statistics with analysis of simple regresion which assisted by computer program SPSS Statistics 17.0 for Windows. The result of this reseach indicates that have an significant influence between emotional quotient toward independence learning. Whereas not have an significant influece between emotional quotient toward comprehension of mathematics.